Analogical grounding of figurative language: narrative and metaphor and the rhetoric of inquiry - M. Elaine Botha (Acta Academica, 2011)
Storytelling requires clear qualification of context if it is to provide solid knowledge. Combining storytelling or narrative with scientific discourse is to some extent incongruous. Stories and narratives thrive on the concrete and often particular experiences of human beings whereas theorising is characterised by abstraction aimed at identifying the laws underlying the regularities observed in reality. Although stories often deal with the individual and particular, the knowledge contained in them refers to classes of phenomena, not to unique individuals. The secret to understanding the prevalence of metaphor in narrative and storytelling is located in the fact that metaphor discloses par excellence the ontic and ontological classifications in reality. It lies at the root of descriptive classification, meaning change and meaning transfer and is grounded in the analogies revealed by the metaphor.